2018
DOI: 10.1186/s12879-018-3036-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of household contacts of pulmonary tuberculosis patients increases case detection in Mwanza City, Tanzania

Abstract: BackgroundTuberculosis (TB) contact tracing is a key strategy for containing TB and provides addition to the passive case finding approach. However, this practice has not been implemented in Tanzania, where there is unacceptably high treatment gap of 62.1% between cases estimated and cases detected. Therefore calls for more aggressive case finding for TB to close this gap. We aimed to determine the magnitude and predictors of bacteriologically-confirmed pulmonary TB among household contacts of bacteriologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 18 publications
(15 reference statements)
6
23
2
1
Order By: Relevance
“…e finding is comparable with the other studies in sub-Saharan Africa (7.8%) [18], Peshawar (0.1-14%) [19], and Tanzania (6.4%) [20], but, higher than that reported from Nepal (1.6%) [21], India (1.15%) [7], Pondicherry of India (4.3%) [22], South Africa (3.9%) [23], and Ethiopia (1%) [24]. e variation might be related to differences in the study population, living situation, and overcrowding which are important risks for respiratory diseases, including tuberculosis [25].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…e finding is comparable with the other studies in sub-Saharan Africa (7.8%) [18], Peshawar (0.1-14%) [19], and Tanzania (6.4%) [20], but, higher than that reported from Nepal (1.6%) [21], India (1.15%) [7], Pondicherry of India (4.3%) [22], South Africa (3.9%) [23], and Ethiopia (1%) [24]. e variation might be related to differences in the study population, living situation, and overcrowding which are important risks for respiratory diseases, including tuberculosis [25].…”
Section: Discussionsupporting
confidence: 88%
“…is study revealed that the likelihood of TB among household contacts eating meals less than three times per day was 4 times higher than that of individuals who eat meals three times or more per day. is is in line with the studies conducted in Tanzania [20] and Pakistan [29]. is might be due to undernutrition or nutritional deficiency that impairs cell-mediated immunity which can lead to progression of latent infection to active TB disease.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, TB treatment supporter characteristics were presented in Table 3. Another study revealed that 7 out of 100 contacts living in the same house with a TB patient developed bacteriologically-confirmed pulmonary TB (Beyanga et al, 2018). This study denoted that household contact with TB patients tended to get contagion of TB transmission without universal protection and functional knowledge.…”
Section: Tb Treatment Supportersmentioning
confidence: 85%
“…Therefore, changing the passive case finding methodology to dynamic case detection strategy is crucial to improving TB case detection in Nigeria [24]. The contacts of infectious TB cases are predictors of TB transmission [58]. Tracking of contacts of TB cases in the community might be a complementary approach in detecting missing cases of TB [59].…”
Section: Epidemiology Of Tuberculosismentioning
confidence: 99%
“…Close proximity to infectious TB disease is key in TB transmission and infection [58]. Related published studies on contact tracing underpin the fact that contact tracking is an active method of detecting supplementary cases.…”
Section: Knowledge Of Contact Tracingmentioning
confidence: 99%